Eriophyoid mites (Acari: Prostigmata) from Brazil: an annotated checklist - Navia, Denise; Duarte, Mercia Elias; Flechtmann, Carlos H. W. (Zootaxa, 2021)
The superfamily Eriophyoidea constitute a group of phytophagous mites of particular economic and evolutionary interest due to their intimate association with host plants and their agricultural importance as harmful or beneficial organisms. Studies on the Eriophyoidea fauna in Brazil started in the early 1900s with botanical works on cecidias and were continued with researchers looking for and reporting on eriophyid mites causing damage to agricultural crops. Therefore, in this annotated checklist, we compile information from just over a century on eriophyid mites reported or described from Brazil. Its purpose is to facilitate plant protection strategies and guide future work on this important group of phytophagous mites. In addition to taxonomy, we present information on host plants and general aspects of cecidia attributed to eriophyoid mites but without genus/species identification. Compilation was based on: i) literature, including papers, books, theses and congress/symposium publications; ii) specimens deposited in mite collections in Brazil. On each species we present: i) suprageneric/generic classification, synonyms and previous genus/era assignments, including references on original and/or additional descriptions; ii) type host plant and other host(s) plant(s) found in the country; iii) host relationships and remarks on symptoms; iv) localities of occurrences at States/Federal District and municipal levels; and v) host plant status in Brazil as well as biomes where they occur or are cultivated. A total of 234 valid eriophyoid mite species are recorded: 196 Eriophyidae, 20 Diptilomiopidae and 18 Phytoptidae, distributed in 92 genera. Host plants comprised 233 species, belonging to 141 genera and 56 plant families. Four new reports of eriophyoid mites in Brazil are presented based on specimens deposited in reference collections. A new combination is presented for Propeaciota secundum (Flechtmann, Amrine & Stasny) in the genus Khanthongella. In addition, data on observations and descriptions of 67 cecidias attributed to eriophyoid mites in five states and on 21 plant families are presented. Geographically, the distribution of species reports of eriophyoids around Brazil is highly uneven, with more than 64% of species (151 spp.) in the Southeast region, which surely reflects a lack of research elsewhere. Regarding host plant specificity, 77.7% are reported on only one host species, 88.9% on one host genus and 98.3% on one host family. Regarding host status 64.1% of species are exclusively associated with native host plants, 27% with naturalized or exotic cultivated host plants, and 6.4% from both native and naturalized or exotic host plants.